2016
DOI: 10.15838/esc.2016.2.44.9
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Concentration of Economic Activity in Russia’s Regions

Abstract: Аннотация. Неравномерность распределения экономической активности на территории России способствует усилению дифференциации ее субъектов по уровню развития. Регионы являются самостоятельными участниками экономических отношений, зачастую выступая не партнерами друг друга, а конкурентами. В более успешных регионах возникают агломерационные эффекты, стимулирующие концентрацию ресурсов, предприятий обрабатывающего производства и сферы услуг, квалифицированных работников, научно-технических знаний. Целью исследован… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It is determined that fixed capital investments have the propensity to concentrate but react strongly to economic crises. Labor resources, by contrast, are distributed relatively evenly, and their con-centration in certain regions is increasing steadily (Rastvortseva & Ternovskii, 2016).…”
Section: Theoretical Basismentioning
confidence: 99%
“…It is determined that fixed capital investments have the propensity to concentrate but react strongly to economic crises. Labor resources, by contrast, are distributed relatively evenly, and their con-centration in certain regions is increasing steadily (Rastvortseva & Ternovskii, 2016).…”
Section: Theoretical Basismentioning
confidence: 99%
“…Mikheeva (2013) noted that diversifi cation tendencies of Russian industry in the regions during the period of 2000-2011 were multidirectional: there was an increase in diversifi cation in half of the regions and decrease in the remaining regions [18]. Rastvortseva и Ternovskii (2016) concluded that spatial concentration of industry by industrial production volume has increased during the period of 1991-2013 [24]. The growth of industry spatial concentration in conditions of the market liberalization that was caused by agglomeration effect could be observed in the post-Soviet Russia as a whole.…”
Section: Spatial Placement Of Industry In the Post-soviet Period: Litmentioning
confidence: 99%
“…Russian research in this area is mostly carried out taking the industrial sector as a case study [12][13][14], including in the field of export specialization of regions [15]. Kutsenko and Eferin [16] found that the largest transformations occurred in the so-called "semiperipheral" regions, and the greatest growth in specialization occurred in the foodprocessing industries.…”
Section: Introductionmentioning
confidence: 99%